INNOVATIVE CULTURE AND PERSONAL VALUES: ENTREPRENEURIAL PERSPECTIVE FROM GRADUATING STUDENTS OF SELECTED PRIVATE UNIVERSITIES IN OGUN STATE, NIGERIA. - Tijani, O.O.; Olubiyi, T.O.; Ishola, T.O. (INTI International University, 2022)
Entrepreneurship edification had been indoctrinated in Nigerian university curriculum, yet many graduates still find it challenging to be self-employed. This appeared to make university support on entrepreneurship to students to be inadequate. Thus, the objective of this paper is to investigate the impact of innovative culture, personal values on graduating students’ entrepreneurial tendency. Survey research design was engaged with data from graduating undergraduates’ students of Babcock, Covenant, Bells and Crawford Universities in Nigeria. A multi-stage sampling technique was used, 394 questionnaires were administered but 379 were duly filled and found usable. The descriptive statistics and regression analysis were employed as methods of data analysis. The result indicated that university’s innovative culture does not have a significant effect on personal values of the students to starting a business (R = 0.026, R2 = 0.001, P=0.412>0.05). This paper therefore concludes that private Universities in Nigeria need to be more supportive and encourage entrepreneurial innovative culture.